Pengelolaan Pendidikan Karakter Bangsa Berbasis Budaya Jawa di TK Negeri Pembina Surakarta - Surani Surani; Bambang Sumardjoko; Sabar Narimo (Manajemen Pendidikan, 2016)
This study aimed to describe the character-based education management Javanese culture as well as enabling and inhibiting factors in TK Negeri Pembina Surakarta. This study uses qualitative research, research design using qualitative descriptive method. Implementation of this research is in the TK Negeri Pembina Surakarta. The data used in this study are primary data and secondary data. Source of the data obtained through interviews and documentation. As a guest speaker in this study was the Principal Teachers and Parents / guardians of students. The validity of the data used in this research is triangulation and source triangulation method. Data were analyzed using interactive analysis. Based on the results of data analysis and discussion we concluded that: 1) The management of education-based character of Javanese culture in TK Negeri Pembina Surakarta carried out by adjusting the curriculum and educational materials charged Javanese culture integrates the material elements of the arts, languages and social systems of Javanese culture, delivering materials charged the value of honesty, humility, discipline, courtesy, cooperation, caring, and responsibility; and deliver material which imparts the principles of respect, harmony, character wise and honest, introspective, low self-esteem, as well as upload form-ungguh and good manners as a form of character Java. 2) The supporting factors in the management of Javanese culture-based character education is education offices and local governments, provision of facilities, committee and parents of students, school management, as well as students coming from the Java community. Factors inhibiting Javanese culture-based education is the lack of standard guidelines for the implementation of educational programs that charged Javanese culture, interests learners to Javanese culture, as well as operate and circumstances on ignorance educators learn less supportive media to use.